2017
DOI: 10.1245/s10434-017-6096-8
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of the Mitophagy-Related Protein Pink1 is Associated with a Poor Response to Chemotherapy and a Poor Prognosis for Patients Treated with Neoadjuvant Chemotherapy for Esophageal Squamous Cell Carcinoma

Abstract: High expression of Pink1 is associated with chemoresistance and a poor prognosis for ESCC patients undergoing neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 31 publications
2
45
0
1
Order By: Relevance
“…Notably, we newly identified PINK1 as a protective prognostic factor in ESCA (esophageal adenocarcinoma) (OS: log rank P = 0.039) ( Figure 3B). This discovery might challenge a previous report stating that high expression of PINK1 is a poor prognostic factor for patients with esophageal squamous cell carcinoma treated with neoadjuvant chemotherapy (35). For HNSC (head and neck squamous cell carcinoma), PINK1 was identified as a protective prognostic factor (OS: log rank P = 0.0072) ( Figure 3C).…”
Section: Prognostic Value Of Pink1 Across Cancersmentioning
confidence: 62%
“…Notably, we newly identified PINK1 as a protective prognostic factor in ESCA (esophageal adenocarcinoma) (OS: log rank P = 0.039) ( Figure 3B). This discovery might challenge a previous report stating that high expression of PINK1 is a poor prognostic factor for patients with esophageal squamous cell carcinoma treated with neoadjuvant chemotherapy (35). For HNSC (head and neck squamous cell carcinoma), PINK1 was identified as a protective prognostic factor (OS: log rank P = 0.0072) ( Figure 3C).…”
Section: Prognostic Value Of Pink1 Across Cancersmentioning
confidence: 62%
“…PINK1 (PARK6) a kinase involved in the regulation of autophagy and the cell cycle, has been involved in glioblastoma, and ovarian cancers (Berthier et al, 2011 ; Devine et al, 2011 ; O’Flanagan et al, 2016 ). Recently, PINK1 expression has been associated with poor response to chemotherapy (Yamashita et al, 2017 ). Mutations in DJ1 (PARK7, a regulator of the tumor suppressor PTEN) is observed in PD patients and in breast, lung, pancreatic, gastric and prostate cancers (Hod, 2004 ; He et al, 2011 ; Zeng et al, 2011 ; Kawate et al, 2013 ; Li et al, 2013 ).…”
Section: Cancer and Parkinson’s Diseasementioning
confidence: 99%
“…Increased mitochondrial turnover would depend on increased fission and mitophagy to eliminate damaged mitochondria, together with increased mitochondrial biogenesis and fusion to repopulate cells with fit mitochondria. Interestingly, a high mitophagic rate has been reported to be associated with chemoresistance in several cancer cell types (Su et al, 2016;Villa et al, 2017;Yamashita et al, 2017;Naik et al, 2018), and Zheng et al (2015) further observed that mitophagy participates in hypoxia-induced radioresistance in breast cancer cell lines. There is also good evidence that a high rate of mitochondrial biogenesis, primarily depending on activation of mitochondrial transcription factor A (TFAM) and transcription coactivator peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), participates in chemoresistance (Gabrielson et al, 2014;Wu et al, 2016;Shen et al, 2018;Hu and Guo, 2019).…”
Section: Discussionmentioning
confidence: 90%